(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
The deposition behaviour of copper ammonia complexes from ore leachate and synthetic copper ammonium sulphate solutions was investigated using cyclic voltammetrywith platinumas counter electrode. The work is carried out to understand the deposition behaviour of the ore for hydrometallurgical and electro winning application. The chemical reduction and deposition of copper from both solutions consisted of two reversible electrochemical processes, each involving the transfer of a single electron. The Cu(NH3)4 2+ complex in the copper leachate is first reduced to Cu(NH3)4 + before being reduced to metallic copper. With synthetic copper ammonium sulphate (Cu(NH3)4SO4), the reduction to metallic copper is a ligand-coupled electron transfer reaction which proceeds as two sequential, single-electron transfer processes. The Cu/Cu(NH3)4 2+ redox reaction during deposition of copper from the leachate is fast compared to that of the Cu/Cu2+ redox reaction in the Cu(NH3)4SO4 synthetic solution. Investigation of the electrochemical kinetics shows that the linear relationship between the peak current and the square root of the scan rate is an indication that the Cu(NH3)4 + and Cu(NH3)4SO4 reduction to Cu proceeds through a diffusion-controlled process. Bangladesh J. Sci. Ind. Res.55(3), 229-236, 2020